2018
DOI: 10.3390/su10030687
|View full text |Cite
|
Sign up to set email alerts
|

Public Perceptions and Willingness to Pay for Renewable Energy: A Case Study from Greece

Abstract: Abstract:The purpose of this study is to discover the factors shaping public opinion about renewable energy sources and investigate willingness to pay for expansion of renewable energy sources in the electricity mix. Data was collected through a questionnaire applied in Nikaia, an urban municipality of Greece. The respondents have a positive attitude towards renewable energy systems. Most of them have good knowledge of solar and wind energy systems and are using solar water heating, while several respondents o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
123
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(138 citation statements)
references
References 64 publications
7
123
0
8
Order By: Relevance
“…The above findings show that policy-makers of both high and low GDP countries should take all the needed measures to increase RES contribution to the energy mix. Such measures involve the creation of a friendly environment for large-scale investments in RESs [46] and the provision of other incentives such as financial facilities to citizens [47][48][49][50]. Financial support is necessary since the richest countries can afford to use RESs.…”
Section: Resultsmentioning
confidence: 99%
“…The above findings show that policy-makers of both high and low GDP countries should take all the needed measures to increase RES contribution to the energy mix. Such measures involve the creation of a friendly environment for large-scale investments in RESs [46] and the provision of other incentives such as financial facilities to citizens [47][48][49][50]. Financial support is necessary since the richest countries can afford to use RESs.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, Al-Mulai et al [34] analysed 108 countries for the period 1980-2009 and established bi-directional causality within 79 per cent of the countries, neutrality hypothesis within 19 per cent of the countries and unidirectional causality from growth to renewable energy within 2 per cent of the countries. In a recent study, Ntanos et al [54] employed autoregressive distributive lag model and analysed the relationship between renewable energy consumption and economic growth for EU countries during the period 2007-2016. They found that the growth hypothesis holds true for countries with a higher level of GDP per capita, while the neutrality hypothesis holds true for countries with lower levels of GDP per capita.…”
Section: Neutrality Hypothesismentioning
confidence: 99%
“…At the Mediterranean basin, in general, and in the Greek context, in particular, a developed, vivid, and extensive literature has been developed on the impacts of energy consumption and possible policies to plan and control energy consumption to alleviate the environmental pollution caused by the ongoing overexploitation of fossil fuels for energy production [1][2][3][4][5]. In the built environment of the Mediterranean basin, it is noteworthy that predictions made by bioclimatic indices differ from actual thermal pleasure, thus, research has been focused on assessing such commonly-used bioclimatic indices that unveil human thermal pleasure, mostly identifying simulated thermal pleasure in a Mediterranean urban environment [6]. Field surveys, weather measurements, and different microclimatic characteristics in Athens, Greece, all unveiled a significant correlation between predicted and actual thermal pleasure, indicating a strong correlation when indices classes were taken into account [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the built environment of the Mediterranean basin, it is noteworthy that predictions made by bioclimatic indices differ from actual thermal pleasure, thus, research has been focused on assessing such commonly-used bioclimatic indices that unveil human thermal pleasure, mostly identifying simulated thermal pleasure in a Mediterranean urban environment [6]. Field surveys, weather measurements, and different microclimatic characteristics in Athens, Greece, all unveiled a significant correlation between predicted and actual thermal pleasure, indicating a strong correlation when indices classes were taken into account [6]. Another index that has been utilized in the relevant literature, specifically for two cities in Brazil, was that of the effective temperature index resulting from the wind effect (ETv) that ranged from partially comfortable to uncomfortable, with a thermal sensation of 27-28 • C in the hours between 12:00 and 14:00 [7].…”
Section: Introductionmentioning
confidence: 99%